High Yield Transfer of Clean Large-Area Epitaxial Oxide Thin Films - Zhang, Bowen; Yun, Chao; MacManus‑Driscoll, Judith L. (Nano-Micro Letters, 2021)
In this work, we have developed a new method for manipulating and transferring up to 5 mm × 10 mm epitaxial oxide thin films. The method involves fixing a PET frame onto a PMMA attachment film, enabling transfer of epitaxial films lifted-off by wet chemical etching of a Sr3Al2O6 sacrificial layer. The crystallinity, surface morphology, continuity, and purity of the films are all preserved in the transfer process. We demonstrate the applicability of our method for three different film compositions and structures of thickness ~ 100 nm. Furthermore, we show that by using epitaxial nanocomposite films, lift-off yield is improved by ~ 50% compared to plain epitaxial films and we ascribe this effect to the higher fracture toughness of the composites. This work shows important steps towards large-scale perovskite thin-film-based electronic device applications. Highlights: 1 A new way to achieve high yield and large area oxide thin film transfer is developed. Three different film compositions are demonstrated: SrRuO3, CeO2, and CeO2/STO nanocomposite films. 2 Cracks, wrinkles, and damages are prevented by the new transfer method. They are commonly introduced by conventional transfer processes. 3 Vertically aligned nanocomposite (VAN) structures can further improve the transfer yield. Possible mechanisms related to increased fracture toughness are proposed. 4 We have opened up a route to large-scale oxide thin-film-based electronic device applications.